(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The continuity of the operations, growth or decrease in the business activities of any company is in line with the on time and optimized funding of cash liquidity and suitable as well as the proper use of them in investment paths in the direction of creating output and ultimately, to increase the shareholders wealth. The goal of this research is to determine the relationship between cash liquidity and abnormal output of stocks. For this purpose, 130 companies were selected by employing simple random method among the companies were enlisted in Stock Exchange Organization. Different cash liquidities included the operational and non-operational cash flows were taken as the five main independent variables, the divisible profits, financial leverage and the size of the company were defined as other independent variables; and, the abnormal output of stock was considered as dependent variable. After analyzing the pre-hypothesis by using combined multi-variable regression and based on the panel data analysis, five linear relations were assessed. The results of the research showed positive relationship between different cash flows, except tax cash flow and the abnormal output of stock. With respect to the determining coefficients which were obtained, the assessed relationship was considered very weak linear relation. The results of T.Student and Fischer showed that the assessed relationship was not significant in the statistical society level. Analyzing the non-parametric correlation showed similar results.